INDONESIAN GRAMMAR IN PETJO - Deanty Rumandang Bulan (Pusat Pengembangan Bahasa IAIN Tulungagung, 2018)
Petjo was created by mixing Dutch and local languages in Dutch East Indisch. This language is the language spoken by the Indos in the Dutch colonial era. It has a unique feature despite being named as ‘broken Dutch’. This present study is a descriptive qualitative study that looks into the feature of Indonesian language grammar in Petjo. This study elaborates the feature of Indonesian grammar in Petjo from morpho-syntax perspective. Results show that there are at least seven characteristics of Indonesian grammar appeared in Petjo. This explains why Petjo is called ‘broken Dutch’.